ANALYSIS OF GROUPS WITH A HIGH-RISK FACTOR FOR THE DEVELOPMENT OF BRONCHIAL ASTHMA IN CHILDREN WHO HAVE EXPERIENCED BRONCHOOBSTRUCTIVE SYNDROME - Umarova Saodat Sulaymonovna; Nabieva Farangiz Sadriddinovna; Bobokulova Aziza Kurashboyevna (Western European Studies, 2024)
Considering the high annual rate of increase in the prevalence of asthma in children, which reaches 20%, currently it remains relevant to study issues devoted to establishing risk factors for the development of biofeedback and identifying their impact on the development of asthma in children. In this connection, it is necessary to search for predicting the course and outcome of AOB and introduce them into the practical activities of doctors, in order to select tactics for examining patients and optimizing treatment and rehabilitation measures
Keywords: BOS; development of asthma; children